Antibiotics and antimicrobial resistance in the COVID-19 era: Perspective from resource-limited settings. (March 2021) - Lucien, Mentor Ali Ber; Canarie, Michael F.; Kilgore, Paul E.; Jean-Denis, Gladzdin; Fénélon, Natael; Pierre, Manise; Cerpa, Mauricio; Joseph, Gerard A.; Maki, Gina; Zervos, Marcus J.; Dely, Patrick; Boncy, Jacques; et al.
Highlights: There has been concern for worsening antimicrobial resistance in COVID-19 patients. The choice of antibiotics in COVID-19 patients is often empiric. The guidelines on antibiotic use in COVID-19 should be adapted to new evidence. Infection prevention control policies can reduce antimicrobial resistance. Antimicrobial stewardship programs can contribute to limiting antimicrobial resistance. Abstract: The dissemination of COVID-19 around the globe has been followed by an increased consumption of antibiotics. This is related to the concern for bacterial superinfection in COVID-19 patients. The identification of bacterial pathogens is challenging in low and middle income countries (LMIC), as there are no readily-available and cost-effective clinical or biological markers that can effectively discriminate between bacterial and viral infections. Fortunately, faced with the threat of COVID-19 spread, there has been a growing awareness of the importance of antimicrobial stewardship programs, as well as infection prevention and control measures that could help reduce the microbial load and hence circulation of pathogens, with a reduction in dissemination of antimicrobial resistance. These measures should be improved particularly in developing countries. Studies need to be conducted to evaluate the worldwide evolution of antimicrobial resistance during the COVID-19 pandemic, because pathogens do not respect borders. This issue takes on even greater importance in developing countries, where data on resistance patterns are scarce, conditions for infectious pathogen transmission are optimal, and treatment resources are suboptimal.